Postsynaptic structure formation of human iPS cell-derived neurons takes longer than presynaptic formation during neural differentiation in vitro - Kazuyuki Togo; Hayato Fukusumi; Tomoko Shofuda; Hiroshi Ohnishi; Hiroyuki Yamazaki; Mariko Kato Hayashi; Nana Kawasaki; Nobuyuki Takei; Takanobu Nakazawa; Yumiko Saito; Kousuke Baba; Hitoshi Hashimoto; et al. (Molecular Brain, 2021)
Abstract The generation of mature synaptic structures using neurons differentiated from human-induced pluripotent stem cells (hiPSC-neurons) is expected to be applied to physiological studies of synapses in human cells and to pathological studies of diseases that cause abnormal synaptic function. Although it has been reported that synapses themselves change from an immature to a mature state as neurons mature, there are few reports that clearly show when and how human stem cell-derived neurons change to mature synaptic structures. This study was designed to elucidate the synapse formation process of hiPSC-neurons. We propagated hiPSC-derived neural progenitor cells (hiPSC-NPCs) that expressed localized markers of the ventral hindbrain as neurospheres by dual SMAD inhibition and then differentiated them into hiPSC-neurons in vitro. After 49 days of in vitro differentiation, hiPSC-neurons significantly expressed pre- and postsynaptic markers at both the transcript and protein levels. However, the expression of postsynaptic markers was lower than in normal human or normal rat brain tissues, and immunostaining analysis showed that it was relatively modest and was lower than that of presynaptic markers and that its localization in synaptic structures was insufficient. Neurophysiological analysis using a microelectrode array also revealed that no synaptic activity was generated on hiPSC-neurons at 49 days of differentiation. Analysis of subtype markers by immunostaining revealed that most hiPSC-neurons expressed vesicular glutamate transporter 2 (VGLUT2). The presence or absence of NGF, which is required for the survival of cholinergic neurons, had no effect on their cell fractionation. These results suggest that during the synaptogenesis of hiPSC-neurons, the formation of presynaptic structures is not the only requirement for the formation of postsynaptic structures and that the mRNA expression of postsynaptic markers does not correlate with the formation of their mature structures. Technically, we also confirmed a certain level of robustness and reproducibility of our neuronal differentiation method in a multicenter setting, which will be helpful for future research. Synapse formation with mature postsynaptic structures will remain an interesting issue for stem cell-derived neurons, and the present method can be used to obtain early and stable quality neuronal cultures from hiPSC-NPCs.